A novel tool to predict in-hospital mortality after hip-fracture: the PRIMOF score. (30th September 2020) - Di Martino, G; Di Giovanni, P; Cedrone, F; D'Addezio, M; Masciarelli, M; Meo, F; Scampoli, P; Staniscia, T
Abstract: Background: Increased life expectancy has led to an increased incidence of hip fractures in aged people. Patients reporting hip fractures often show relevant comorbidities leading to prolonged hospital stays, significant complications, and higher mortality rates. Being aware of the factors associated with in-hospital death or adverse events can help patients and healthcare providers make informed planning and management. The aims of this study were the development and validation of a score predicting in-hospital mortality among hip fractured patients. Methods: Patients were selected from the hospital discharge record referring to the period 2006-15 and including data on the population aged 40 years or over in Abruzzo, a region of Southern Italy. The whole population was divided into 2 random samples in order to control the accuracy of predictions and to increase the reliability of all the statistical analyses. A multivariate logistic regression model was performed to identify the predictors of in-hospital mortality. All the diagnoses significantly associated with in-hospital mortality were included in the final model. Results: The score ranged between 0 and 27 and was divided into four groups to facilitate the tool interpretation. An increase in odds ratio values was documented alongside the increase in PRIMOF score both in training and in validation groups. The score showed a good calibration and a good accuracy in predicting in-hospital mortality. Conclusions: This study has shown that a simple score, based on the clinical history of the patient, allows to stratify the risk of hip fractured population in terms of in-hospital mortality. The identification of individuals at high risk of short-term death can be of great significance to health providers and public and private health services. Key messages: Patients reporting hip fractures often show relevant comorbidities leading to higher in-hospital mortality rates. A simple score, based on the clinical history of the patient, allows to stratify the risk of hip fractured population in terms of in-hospital mortality.